PENGARUH BENCANA ALAM, PERUBAHAN IKLIM, DAN KUALITAS LINGKUNGAN TERHADAP JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA KE INDONESIA - Safitri Safitri; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research goal is looking for the effect of natural disaster, climate change, and environment quality to the amount of tourist visit to Indonesia. This research uses panel data from 2014 untill 2017, the data get from the related institutions, and uses multiple regression analysis. This research result: 1) Natural disaster has negative influence and it is not significant to tourist visit to Indonesia, 2) Climate change has positive and significant influence to tourist visit to Indonesia, and 3) Environment quality has positive influence and is not significant to the amount of torist visit to Indonesia.